Some techniques in micropropagation and breeding of Paphiopedilum spp. - Tung, Hoang Thanh; Luan, Vu Quoc; Nhut, Duong Tan (Vietnam Journal of Science and Technology, 2020)
Paphiopedilum orchids are one of the most popular and rare orchid genera sold and exhibited as pot plants and cut flowers. Their wild populations are under the threat of extinction as a result of over-collection and loss of suitable habitats. Reduction in their commercial value through large-scale propagation in vitro is a preferable option to reduce pressure from illegal collection, to attempt at meeting commercial needs and to re-establish these threatened orchid species back into the wild. Although they are commercially propagated via seed germination in vitro, Paphiopedilum are considered to be difficult to propagate in vitro, especially by plant regeneration from tissue culture. This paper aims to provide the most important techniques on Paphiopedilum propagation mainly including plant, cell, tissue and organ culture techniques applied to in vitro propagation of Paphiopedilum and to emphasize the importance of further improving tissue culture protocols from ex vitro-derived explants of mature plants.